Endodontic Management of An Unusual Mandibular First Molar with Six Canals: A Case Report and Systematic Review - Ahmad, Sarah; Andrabi, Syed Mukhtar -Un- Nisar; Kumar, Ashok; Mishra, Surendra Kumar; Tewari, Rajendra Kumar (Journal of Dentistry Indonesia, 2022)
The permanent mandibular first molar is frequently involved in conventional root canal treatment due to its function and position in the oral cavity. Additional root canals mandate accurate diagnosis and conservative management to prevent any procedural errors. The first independent middle mesial canal incidence was verified in mandibular molars in 1974, with a global incidence of 10.8–27.0%. Reporting of the middle distal canal in the endodontic literature is scarce, with an incidence of 0.2–3%. The present case report describes the endodontic management of an unusual permanent mandibular first molar with three canals in the mesial and distal roots, diagnosed with irreversible pulpitis and apical periodontitis. A dental operating microscope and multiple angulated radiographs were used to identify the unusual morphology, and this was confirmed with cone-beam computed tomography imaging. The access cavity was modified to a trapezoidal shape, and the pulp chamber was carefully explored following root dentinal maps to expose additional canals by ultrasonic troughing. Incorporating a dental operating microscope and cone-beam computed tomography imaging in routine endodontic cases facilitates a better understanding and visualization of the complex root canal anatomy, making even the management of endodontically challenging cases more predictable.